On the Spectrum of Certain Hadamard Manifolds - Ballmann, Werner; Mukherjee, Mayukh; Polymerakis, Panagiotis (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
We demonstrate the absolute continuity of the spectrum and determine the spectrum as a set for two classes of Hadamard manifolds, as well as for specific domains and quotients of one of these classes.